Elevated levels of endothelial cell-derived microparticles following short-term withdrawal of continuous positive airway pressure in patients with obstructive sleep apnea: data from a randomized controlled trial. - Ayers, L; Stoewhas, A; Ferry, B; Stradling, J; Kohler, M (2013)
BACKGROUND: Obstructive sleep apnea has been associated with impaired endothelial function; however, the mechanisms underlying this association are not completely understood. Cell-derived microparticles may provide a link between obstructive sleep apnea and endothelial dysfunction. OBJECTIVES: This randomized controlled trial aimed to examine the effect of a 2-week withdrawal of continuous positive airway pressure (CPAP) therapy on levels of circulating microparticles. METHODS: Forty-one obstructive sleep apnea patients established on CPAP treatment were randomized to either CPAP withdrawal (subtherapeutic CPAP) or continuing therapeutic CPAP, for 2 weeks. Polysomnography was performed and circulating levels of microparticles were analyzed by flow cytometry at baseline and 2 weeks. RESULTS: CPAP withdrawal led to a recurrence of obstructive sleep apnea. Levels of CD62E+ endothelium-derived microparticles increased significantly in the CPAP withdrawal group compared to the continuing therapeutic CPAP group (median difference in change +32.4 per µl; 95% CI +7.3 to +64.1 per µl, p = 0.010). CPAP withdrawal was not associated with a statistically significant increase in granulocyte, leukocyte, and platelet-derived microparticles when compared with therapeutic CPAP. CONCLUSIONS: Short-term withdrawal of CPAP therapy leads to a significant increase in endothelium-derived microparticles, suggesting that microparticle formation may be causally linked to obstructive sleep apnea and may promote endothelial activation.